PENGELOLAAN MEDIA SOSIAL UNTUK MENDUKUNG AKTIVITAS HUMAS PEMERINTAH KOTA SURAKARTA - Trias Yulvia; Hery Sawiji; Patni Ninghardjanti (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2020)
The study aims to find out Social media management to supporting activities public relations and protocol division of Surakarta city government and obstacles and solutions faced in social media management to supporting activity public relations and protocol division of Surakarta city government. The method used in this study used a qualitative method with a descriptive. Data in this study was obtained from informant, research locations and documents. Sampling technique using purposive sampling . The validity test used  data  triangulation  and  method  triangulation.  Based  on  the  research results, Management of social media conducted by the public relations and protocols of the city of Surakarta will consist of planning, social media management activities, social media management strategies, the implementation of social media management, The monitoring and evaluation. Constraints on social media management are limited to human resources and the time limit for reserving social media, while the solution to the problem of managing social media is that it provides employees in the public relations and protocol of the city of Surakarta and has responded to a message given by its own urgenst.